Implications of Teaching Experience in Internship Program III in Developing Pedagogical Competence of Prospective Student Teachers - Baiti Sadiah; Norlela Norlela; Norhayatun Norhayatun (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The main objective of this study is to explore the impact of teaching experience in the Internship Program III on improving the pedagogical competence of student teachers in the Economics Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Sampit, Academic Year 2024/2025. A descriptive qualitative method was applied in this study. The subject determination was carried out through a purposive sampling technique, involving three students who had completed Internship Program III, plus one supporting informant. Information gathering was based on semi-structured interviews. Furthermore, the data were analyzed using NVivo 12 software by maximizing the Word Frequency Query Results and Text Search Query features, which were then applied and visualized into a Word Tree and Word Cloud. To ensure the validity of the data, the researcher implemented a source triangulation procedure. The research findings indicate the implications of student teaching experience in the Internship Program III on the pedagogical competence of student teachers. Specifically, this teaching experience facilitates students in mastering various aspects ranging from understanding educational insights and foundations, student characteristics, curriculum development, learning planning and implementation, utilization of learning technology, evaluation of learning outcomes, and development of student potential. Thus, Internship III has proven effective as a bridge that synergizes theory in the classroom as crucial preparation before entering the world of teaching.